A Cross-Sectional Decision-Making Approach to Inform Neuropsychological Battery Development in Professional Hockey. (20th December 2021) - Bruce, Jared M; Meeuwisse, Willem; Thelen, Joan; Hutchison, Michael G; Comper, Paul; Echemendia, Ruben J
Abstract: Objective: Neuropsychologists commonly use a large battery of tests to inform clinical decisions. Decision analysis can be used to determine which individual tests play a role in the decision-making process. The objective of this project was to conduct quantitative and qualitative decision analysis of decisions by team neuropsychologists with professional hockey players being evaluated as part of the National Hockey League (NHL)/NHL Players Association Concussion Protocol. Method: We extracted neuropsychological data from an NHL clinical program database. Team neuropsychologists evaluated concussed players using a hybrid neuropsychological test battery. The neuropsychologists then determined whether players were experiencing concussion-related cognitive difficulties. Logistic regression was used to examine which tests accounted for unique variance in the decision-making process. We also conducted a survey of NHL neuropsychologists, asking them to rate the usefulness of each test in the battery. Results: Five of the fifteen measures accounted for unique variance in team neuropsychologists' decisions, including the ImPACT Verbal Memory Composite, Visual Motor Composite, Reaction Time Composite, Symptom Score, and Brief Visuospatial Memory Test—Revised Delayed Recall. Notable discrepancies were uncovered between quantitative indications of usefulness and self-reported qualitative perceptions of test usefulness when making decisions. Qualitatively, clinicians reported that the Hopkins Verbal Learning Test—Revised, Symbol Digit Modalities Test, ImPACT Reaction Time, and Color Trails 2 were the most useful tests when making decisions. Conclusions: Along with validation studies, decision analysis can be used as part of a comprehensive evaluation process to inform the development of best-practice batteries for use among athletes with sports concussion.